(untitled) (Journal of The Colloquium for Information Systems Security Education, 2014)
Cybersecurity competitions are used in higher education to recruit, educate and assess students. Winners of competitions are recognized based on endgame conditions or rules. Uncovering factors that correlate with success in competitions is difficult and less studied. Some literature exists that investigates competition success relative to institutions, there is no existing investigation of success relative to individual participants. Therefore, this research examined one potential factor related to success of competition participants. Specifically, the study measured the degree of relationship between CLI commands and the percentage of challenges completed. Participants consisted of 100 competitors who engaged in a competition. CLI commands, data mined from Linux command history files, were analyzed. The results demonstrated two strong positive relationships and one negligible relationship. Educators may be interested in these results as a means for performance measurement. Likewise, researchers may leverage these findings to configure game conditions or conduct future causal studies.